EXAMINATION OF THE INFLUENCE OF RIBS ON THE ACOUSTIC PROPERTIES OF THE DECKS FOR GUITARS - Bardarov, Nicolay; Nakov, Alexander (Innovation in Woodworking Industry and Engineering design, 2012)
The quality of musical instruments depends not only on good wood, but the way of con-struction of oscillating parts. The work examines the impact of size and location of the ribs on the distribution of the resonance of the decks for guitars. It was tested four decks for classical guitar. Consistently was measuring the acoustic characteristics of each of the boards building decks. It was followed the change of resonances after putting the ribs of the main schemes. It was established the influence of painting on the decks of the frequency and amplitude of the resonance.